Review of modern applications of solar cells in communication systems - Mohammed, Najat Shyaa; Ibrahim, Raheek (Anbar Journal of Engineering Science, 2022)
Designing an integrated communications system with efficient features is important to researchers and designers. This paper deals with a review of the most important technologies and applications that combine solar cells and communication systems such as Li-Fi technology and its principle of operation, which is a wireless system in which the optical signal is used as a carrier signal as an alternative to the traditional radio frequencies used in Wi-Fi networks, where Li-Fi relies on LED to transmit data, and at high speeds that exceed Wi-Fi technology. Solar Power Satellite (SPS) technology where the satellite is placed in a geostationary orbit in the equatorial plane. As well as the application of photovoltaic solar cells in the SOLPLANT planar antenna, and the replacement of the radiating element of the antenna with a solar cell. The solar cell can transmit and receive electromagnetic signals as well as generate direct current and can be used as antennas either as a single solar cell or group cells and has wide applications in wireless, mobile, Bluetooth and satellite systems. The solar cell has also been applied in Micro strip antenna called Solan , where the solar cell antenna can be considered as a platform for many communication applications and can also be adopted as a radio frequency transmitter and receiver. As well as the design of many antennas integrated with solar cells and compatible with the 5G communication system , in addition to the presence of many applications that combined smart phones and solar cells. This study showed that these technologies and applications provided clean, safe, high-efficiency, high-speed, data-transferring communication systems with low cost.